Specific actin (ACTC1) missense variants are associated with different overlapping clinical phenotypes and outcomes. (14th October 2021) - Valverde, M; Garcia Hernandez, S; Brogger, M N; Fernandez, G; Cardenas, I; Garcia-Gustiniani, D; Fernandez, X; Lamounier, A; Ochoa, J P; Ortiz-Genga, M; Monserrat, L; McKenna, W
Abstract: Introduction: Pathogenic variants in ACTC1 have been associated with hypertrophic (HCM), dilated (DCM), and left ventricular non-compaction (LVNC) cardiomyopathies. Phenotypes often overlap and atrial septal defects have also been reported. Prognostic data on carriers of these variants are scarce. Methods and results: The proprietary database of a cardiovascular genetic laboratory was examined to assess penetrance and survival in the 438 carriers (191 families) of 75 missense variants in ACTC1 associated with disease. Their mean age at diagnosis was 32.4 (±18.7) years; 52% were male. The diagnosis was isolated HCM in 47%, LVNC in 17%, and DCM in 9%. LVNC with either HCM or DCM was present in an additional 8%; 13% had an atrial septal defect. Among carriers with echocardiographic information, left ventricular dilatation and dysfunction were described in 13% and 16%, respectively. Ventricular arrhythmias and conduction defects were reported in 94 and 93 carriers. Percentages have not been calculated for the latter, as we cannot ensure a denominator in whom cardiac conduction defects and arrhythmias were certainly discarded. Overall, 50% of carriers were diagnosed by age 45, and 10% had experienced a major cardiac event. The p.Leu10Met and p.His90Tyr variants (23% of all carriers) demonstrated lower penetrance and a better prognosis than the p.Glu101Lys variant and the other missense variants. Conclusions: Missense variants in ACTC1 are associated with a range of phenotypes that often overlap. Overall, penetrance and outcomes are age-dependent with a moderate rate of major cardiac events, which are highly dependent on the specific disease-causing variant FUNDunding Acknowledgement: Type of funding sources: None.